Hubungan Faktor Riwayat Diabetes Melitus dan kadar Gula Darah Puasa dengan Kejadian Diabetes Melitus Tipe 2 pada Pasien Usia 25-64 Tahun di Puskesmas Kendal Kerep Kota Malang - Gayatri, Rara Warih (citeus, 2019)
Diabetes mellitus (DM) is one of the systemic diseases that manifests in the oral cavity. One effort to prevent type 2 diabetes is through surveillance activities to determine the associated risk factors. The purpose of this study was to determine the relationship of risk factors for history of diabetes mellitus and fasting blood sugar levels with the incidence of type 2 diabetes mellitus at Puskesmas Kendal Kerep in Malang City. This study used a quantitative descriptive method with cross-sectional design and was conducted at the Puskesmas Kendal Kerep in Malang City, April 2017. The sampling method used was the quota sampling method with the measured variables: the prevalence of diabetes mellitus, a history of diabetes mellitus and levels fasting blood sugar. Data collection techniques used were interview and measurement of fasting blood sugar levels. The research instrument used were Glucko Blood Meter devices and questionnaires. Data processing includes the process of editing, coding, scoring, data entry and cleaning. Data analysis used were univariate and bivariate. The conclusion of the study is that there is a significant relationship between history of Diabetes Mellitus and GDP levels with type 2 DM.